AN ANALYSIS OF THE CORRELATION OF CONSUMER PURCHASE PATTERNS USING APRIOPRI METHOD (A CASE STUDY OF CV. VIFOR CIPTA SOLUSI) - Junianto Bagas Prasetyo; Mutaqin Akbar (Institut Teknologi Dirgantara Adisutjipto, 2020)
CV. Vifor Cipta Solusi is a company that provides electronic equipment. The competition in business, especially among companies providing electronic equipment, is growing. To increase sales of the products, business people in this field need to set a strategy. This research applied the data mining with association technique to find out strong combinations between items. Apriori algorithm is part of the association method in data mining which aims to find out frequent item sets from a certain set of data. The apriori algorithm process is carried out by determining frequent itemsets that meet the requirements of the predetermined minimum support and minimum confidence. From these two measurements, the final association rule can be obtained by which the value of the accuracy (validity) of the association is calculated using the lift ratio. This research obtained 2 association rules with item attributes totaling 294 types of products from 20 main attributes with 1813 records processed from 5282 raw transaction data from January to December 2019. The strong rules obtained are MagnetToner HP Laserjet 85 A, Drum Toner HP Laserjet 85 A => HP Laserjet 85 A toner with a support value of 3.42%, and a confidence value of 81.58% with a lift ratio of 5.00.If a consumer buys an HP Laserjet 85 A MagnetToner and a HP Laserjet 85 A Toner Drum, the consumer will also buy an HP Laserjet 85 A Toner.